2008
DOI: 10.1088/0953-8984/20/14/145207
|View full text |Cite
|
Sign up to set email alerts
|

Structural and transport properties of GaAs/δ-Mn/GaAs/InxGa1−xAs/GaAs quantum wells

Abstract: We report results of investigations of the structural and transport properties of GaAs/Ga1−xInxAs/GaAs quantum wells (QWs) having a 0.5–1.8 monolayer (ML) thick Mn layer, separated from the QW by a 3 nm thick spacer. The structure has hole mobility of about 2000 cm2 (V s)−1, being by several orders of magnitude higher than in known ferromagnetic two-dimensional (2D) structures. The analysis of the electro-physical properties of these systems is based on detailed study of their structure by means of high-resol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 37 publications
2
22
0
3
Order By: Relevance
“…Comprehensive studies of magnetic, structural and transport properties of such structures [16] have revealed an anomalous Hall effect (AHE) and a magnetic hysteresis, which evidence an FM ordering with T c $ 30-35 K. Thus, one could expect manifestation of the ferromagnetism in optical properties, particularly in P c . It is difficult to predict a priori the possible FM effect in this case and it requires special investigations.…”
mentioning
confidence: 99%
“…Comprehensive studies of magnetic, structural and transport properties of such structures [16] have revealed an anomalous Hall effect (AHE) and a magnetic hysteresis, which evidence an FM ordering with T c $ 30-35 K. Thus, one could expect manifestation of the ferromagnetism in optical properties, particularly in P c . It is difficult to predict a priori the possible FM effect in this case and it requires special investigations.…”
mentioning
confidence: 99%
“…However, if the magnetic center posess a bound state with an energy level matching the delocalized carriers energy range, the indirect exchange is dramatically increased due to resonant tunneling effect 6,7 . This phenomenon was observed in GaAs based heterostructures having an In x Ga 1−x As quantum well (QW) and Mn δ-layer in the vicinity of QW [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 79%
“…Однако для потенциальной интеграции ферромагнитных (ФМ) полупроводниковых устройств в существующие техно-логии принципиально важным является исследование магнитных систем с двумерным спектром носителей за-ряда. Результаты исследований магнитных гетерострук-тур позволили частично выяснить особенности таких систем, в том числе, в случае пространственного разде-ления магнитных атомов Mn и двумерного дырочного газа, когда их взаимодействие является существенно непрямым [3][4][5][6][7]. Наличие этого взаимодействия долж-но оказывать заметное влияние на зарядовый транс-порт в системе, однако природа наблюдаемых особен-ностей магнетотранспорта еще далека от детального понимания.…”
unclassified
“…Образцы были выращены на подложках GaAs методом MOCVD (metalorganic chemical vapour deposition) с лазерным распылением Mn-мишени, после чего на поверхности образцов бы-ли сформированы мезаструктуры в виде холловских мостиков (с отношением длины канала к его ши-рине ≈ 5). Структура исследованных образцов пред-ставлена в [4,13]. Ввиду диффузии атомов марган-ца в процессе роста структуры формируется примес-ный слой (Ga, Mn)As толщиной 3−5 нм, отделенный от квантовой ямы спейсером GaAs толщиной 3 нм.…”
unclassified
See 1 more Smart Citation